أثر التركيب الطارئ على الكلمة بدخول ما الكافة - عبدالرشيد عبدالله فاطمة (Journal of College of Education, 2019)
There are two types for construction (tarakib): situational production which is created constructively by the language composer, so it comes attached to the word, and incidental construction that is unusual to usage without any producer’s roll. It affects the word as it may provide a new syntactical rule or new meaning that it never had before. This paper is interested in investigating the affect of incidental construction as a result of attaching "suspending Ma" "Ma Al Kaffah" to a word citing scholars’ sayings and the disagreement on the its affect. According to Ibn Hisham, "Ma Al kaffah" comes on three types: "Ma" that suspends what it is attached to from (nassb) and (raf), "Ma" which suspends what it is attached to from (raf), and "Ma" that suspends what it is attached to from (jarr). The study reached a number of results, the most important of which are: Grammarian showed disagreements in regard to activating "inna" and its sisters after adding suspending (ma) to them and they have four opinions, two of which are: • According to Ibn Malik, (ma) with (alkaf) indicates reasoning. According to Sibawayh, (ba) attached (ma) is equivalent to (rubbama).